Fabrication of Hydrophobic Multilayered Fabric for Passive Daytime Radiative Cooling. Issue 4 (12th January 2022) - Ji, Yating; Sun, Yilan; Muhammad, Javed; Li, Xiaoyan; Liu, Ziqiang; Tu, Pengpeng; Wang, Youquan; Cai, Zaisheng; Xu, Bi
Abstract: Passive daytime radiative cooling (PDRC) has attracted great attention recently due to its high potential for reducing global energy consumption. However, PDRC materials are easily contaminated in practical applications, which will seriously attenuate their long‐term cooling performance. In this work, a multilayered PDRC fabric that is composed of polydimethylsiloxane (PDMS), polymethyl methacrylate (PMMA), and cotton is shown. This multilayered fabric displays a high solar reflectivity (0.94) and an appropriate atmospheric window emissivity (0.79). A practical application test demonstrates the glass covered by this PDRC fabric can lower the temperature up to 7.8 °C under a solar intensity of ≈495 W m −2 . Meanwhile, the multilayered PDRC fabric exhibits self‐cleaning property due to its high water contact angle of 118°. Rolling water can effectively remove the contaminants on the fabric surface. It is believed that this multilayered fabric is a promising material to alleviate the energy crisis and reduce greenhouse gas emissions. Abstract : Hydrophobic multilayered fabric is used for passive building cooling. It shows sufficiently high solar reflectivity (0.94) and good emissivity (0.79) and the cooling effect is 7.8 °C compared to the blank group. The hydrophobic surface ensures self‐cleaning performance. The addition of polymethyl methacrylate film prepared with spray gun is the key factor to improve the solar reflectivity.